Association of ventricular arrhythmia and in-hospital mortality in stroke patients in Florida: A nonconcurrent prospective study. Issue 28 (July 2017) - Dahlin, Arielle A.; Parsons, Chase C.; Barengo, Noël C.; Ruiz, Juan Gabriel; Ward-Peterson, Melissa; Zevallos, Juan Carlos
Abstract : Abstract: Stroke remains one of the leading causes of death in the United States. Current evidence identified electrocardiographic abnormalities and cardiac arrhythmias in 50% of patients with an acute stroke. The purpose of this study was to assess whether the presence of ventricular arrhythmia (VA) in adult patients hospitalized in Florida with acute stroke increased the risk of in-hospital mortality. Secondary data analysis of 215, 150 patients with ischemic and hemorrhagic stroke hospitalized in the state of Florida collected by the Florida Agency for Healthcare Administration from 2008 to 2012. The main outcome for this study was in-hospital mortality. The main exposure of this study was defined as the presence of VA. VA included the ICD-9 CM codes: paroxysmal ventricular tachycardia (427.1), ventricular fibrillation (427.41), ventricular flutter (427.42), ventricular fibrillation and flutter (427.4), and other – includes premature ventricular beats, contractions, or systoles (427.69). Differences in demographic and clinical characteristics and hospital outcomes were assessed between patients who developed versus did not develop VA during hospitalization (χ 2 and t tests). Binary logistic regression was used to estimate unadjusted and adjusted odds ratios and 95% confidence intervals (CIs) between VA and in-hospital mortality. VA was associated with an increased risk of in-hospital mortality after adjusting for all covariates (odds ratio [OR]: 1.75; 95% CI: 1.6–1.2). There was an increased in-hospital mortality in women compared to men (OR: 1.1; 95% CI: 1.1–1.14), age greater than 85 years (OR: 3.9, 95% CI: 3.5–4.3), African Americans compared to Whites (OR: 1.1; 95% CI: 1.04–1.2), diagnosis of congestive heart failure (OR: 2.1; 95% CI: 2.0–2.3), and atrial arrhythmias (OR: 2.1, 95% CI: 2.0–2.2). Patients with hemorrhagic stroke had increased odds of in-hospital mortality (OR: 9.0; 95% CI: 8.6–9.4) compared to ischemic stroke. Identifying VAs in stroke patients may help in better target at risk populations for closer cardiac monitoring during hospitalization. The impact of implementing methods of quick assessment could potentially reduce VA associated sudden cardiac death.